2023
DOI: 10.3390/cancers15061876
|View full text |Cite
|
Sign up to set email alerts
|

Support Tools in the Differential Diagnosis of Salivary Gland Tumors through Inflammatory Biomarkers and Radiomics Metrics: A Preliminary Study

Abstract: Background: The purpose of this study was to investigate how the systemic inflammation response index (SIRI), systemic immune-inflammation index (SII), neutrophil/lymphocyte ratio (NLR) and platelet/lymphocyte ratio (PLR), and radiomic metrics (quantitative descriptors of image content) extracted from MRI sequences by machine learning increase the efficacy of proper presurgical differentiation between benign and malignant salivary gland tumors. Methods: A retrospective study of 117 patients with salivary gland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Urbanowicz et al reported that SIRI levels higher than 1.22 had a higher probability of single and complex coronary disease [ 19 ]. Committeri et al used inflammatory markers to differentiate Warthin tumors from pleomorphic adenoma and malignant neoplasms [ 20 ]. They reported SIRI with an accuracy of 0.83 and significant differences in the univariate Kruskal–Wallis test.…”
Section: Discussionmentioning
confidence: 99%
“…Urbanowicz et al reported that SIRI levels higher than 1.22 had a higher probability of single and complex coronary disease [ 19 ]. Committeri et al used inflammatory markers to differentiate Warthin tumors from pleomorphic adenoma and malignant neoplasms [ 20 ]. They reported SIRI with an accuracy of 0.83 and significant differences in the univariate Kruskal–Wallis test.…”
Section: Discussionmentioning
confidence: 99%
“…In other fields of medicine, especially in oncology, radiomic analyses using statistical learning methods by analysing ultrasound [53,54], computed tomography [55][56][57], magnetic resonance [58,59], or positron emission tomography [60] images are very useful for differentiating between cancer and inflammation [61].…”
Section: Discussionmentioning
confidence: 99%
“…Several diagnostic methods are currently studied for establishing diagnosis and guiding the treatment strategy for salivary gland tumors. Morphological parameters like inflammatory biomarkers and radiomics extracted from imaging techniques or from histopathological slides are analyzed as possible targets in establishing diagnosis [ 61 , 65 ].…”
Section: Artificial Intelligence Algorithms In Salivary Gland Tumor D...mentioning
confidence: 99%